The Mnemonic Effects of Novelty and Appropriateness in Creative Chunk Decomposition Tasks - Wu, Xiaofei; Liu, Yu; Luo, Jing (Frontiers in Psychology, 2018)
Creativeness has been widely recognized as the ability to generate thoughts that are both novel (new) and appropriate (useful) (Barron, 1955). In this paper, we investigated the mnemonic effects of novelty and appropriateness in chunk decomposition tasks. Study 1 and study 2 utilized classical recognition tasks (explicit memory) and ambiguous word identification tasks (implicit memory) to reveal whether novelty and appropriateness are involved in different mnemonic systems. A 2 (familiarity) × 2 (appropriateness) experimental design was utilized in our experiments, and the 4 conditions were familiar-appropriate, familiar-inappropriate, novel-appropriate and novel-inappropriate. The results indicated that insight induced by novelty (novel-appropriate condition) has a better performance than other conditions; and further, found an interesting phenomenon of Zeigarnik-like effect which referred to remembering uncompleted tasks better than completed tasks (Zeigarnik, 1927). We further conducted study 3 to ask participants to recall the encoding process (how the characters had been decomposed in the learning stage)，which was more sensitive to Zeigarnik effect and indicated that performance of familiar-appropriate condition (uncompleted tasks) was better than other conditions.